Pemanfaatan Umbi Ganyong Dan Kulit Kacang Tanah Sebagai Bahan Baku Bioplastik Dengan Penambahan Gliserol - Dwi Utami, Fatiya; , Dra. Aminah Asngad, M.Si (2017)
Bioplastics are plastics which can be degraded by microorganisms and is made from renewable materials. Plastic film is made from rasio of canna starch and peanuts peel also glycerol as plasticizer. The purpose of this reasearch is to know the tensile strength, elongation and bioplastic degradation. The reaserch method used completely randomized design by two factors, the first factor was the ratio of starch canna and cellulose peanut peel that were 9.5 g : 0.5 g ; 9 g : 1 g; and 8.5 g : 1.5 g and the second factor was glycerol concentration of 8%, 7%, and 6 %. Analysis of bioplastics showed that test tensile strength, elongation and time degraded. The research results was bioplastics starch-cellulose ratio (9.5 g : 0.5 g ) on the addition of glycerol 6 % produced the best plastic tensile strength values of 1,39 N/mm2, best elongation value 21.3% and degraded 1 week. Keyword : Starch canna, peanut peel, glycerol and bioplastics